Rwanda : Can Performance Pay for Teachers Improve Students’ Learning? - World Bank (World Bank, Washington, DC, 2021)
Performance pay for teachers generates debate. Proponents argue that many school systems have low levels of accountability and advocate incentivizing teachers by linking their pay to either their own efforts or their students’ learning. Critics, however, raise concerns that performance pay attracts people to the teaching workforce who are in it for the money and can diminish the intrinsic motivation to teach among teachers already in classrooms.